Synergistic effects of hypoxia and increasing CO2 on benthic invertebrates of the central Chilean coast - Steckbauer, Alexandra; Ramajo, Laura; Hendriks, Iris E.; Fernandez, Miriam; Lagos, Nelson; Prado, Luis; Duarte, Carlos M. (Frontiers in Marine Science, 2015)
Ocean acidification (OA) and hypoxic events are an increasing worldwide problem, but the synergetic effects of these factors are seldom explored. However, this synergetic occurrence of stressors is prevalent. The coastline of Chile not only suffers from coastal hypoxia but the cold, oxygen-poor waters in upwelling events are also supersaturated in CO2, a study site to explore the combined effect of OA and hypoxia. We experimentally evaluated the metabolic response of different invertebrate species (2 anthozoans, 9 molluscs, 4 crustaceans, 2 echinoderms) of the coastline of central Chile (33°30′S, 71°37′W) to hypoxia and OA within predicted levels and in a full factorial design. Organisms were exposed to 4 different treatments (ambient, low oxygen, high CO2, and the combination of low oxygen and high CO2) and metabolism was measured after 3 and 6 days. We show that the combination of hypoxia and increased pCO2 reduces the respiration significantly, compared to a single stressor. The evaluation of synergistic pressures, a more realistic scenario than single stressors, is crucial to evaluate the effect of future changes for coastal species and our results provide the first insight on what might happen in the next 100 years.